Lalli; Tuomas piispa; Maunu Tavast - Leino, Eino, 1878-1926 (Salt Lake City, UT : Project Gutenberg, 2004)
"Lalli; Tuomas piispa; Maunu Tavast" by Eino Leino is a collection of dramatic works written during the early 20th century. The first piece, "Lalli," is set in 1158 AD and presents a tale focusing on Lalli, a peasant, and his family within a backdrop of societal struggle and impending religious change brought about by the Christianization of Finland. Central characters include Lalli himself, his wife Kerttu, and their daughter Sinikka, reflecting the tension between traditional pagan beliefs and the emergence of Christianity in their lives. The opening of "Lalli" introduces us to a winter evening in Lalli's home, where he and his wife Kerttu engage in a dialogue filled with underlying tension regarding their daughter Sinikka's growing interest in the woods, hinting at a potential romance with a woodsman named Inko. Kerttu expresses concern for their daughter$1 (Bs safety and her changing affections, while Lalli remains somewhat dismissive of both the dangers of the woods and the threats posed by a changing world. Their conversation reveals cracks in the family's dynamics, especially concerning Lalli's stern demeanor, which has created fear in Sinikka. As the scene unfolds, the tension builds toward themes of familial loyalty, the clash of old traditions with new ideologies, and the personal turmoil each character faces, setting the stage for the struggles that lie ahead in the narrative. (This is an automatically generated summary.)s
Release date is 2004-12-24
Produced by Tapio Riikonen
Keywords: Finnish drama